The artful way to plant-based cooking : nourishing recipes and heartfelt moments - Crane-Leroux, Chloé, 1994-; Crane, Trudy, 1959- (Simon Element, an imprint of Simon & Schuster, 2024)
A unique collection of plant-based recipes from the mother-and-daughter duo who were inspired by the simple beauty and delicious meals throughout their travels.